Religious Doubt and Mental Well-Being in Later Life: Is Humility a Protective Resource? - Upenieks, Laura (Journal of psychology and theology, 2024)
This study sought to integrate the study of virtue into the study of religious doubt and mental health by considering how a salient virtue, humility, may moderate the relationship between religious doubt and lower mental well-being. Drawing on data from a national sample of midlife and older adults (N = 1,443) from the United States, regression results suggest that religious doubts were associated with greater depression and lower life satisfaction, and that humility was independently associated with lower depression and greater life satisfaction. Humility was also found to buffer the pernicious association between religious doubt and both indicators of mental well-being. Taken together, our study makes an important contribution by adding the study of the virtue of humility to a growing body of work on religious doubt. The process of dealing with religious doubt is complex and difficult, but the attempt to develop the virtue of humility may be efficacious in thwarting the deleterious consequences of managing the ebbs and flows of faith.